Ethical concerns in court-connected online dispute resolution - QUEK ANDERSON, Dorcas (Institutional Knowledge at Singapore Management University, 2019)
This article examines the burgeoning trend of creating court ODR systems, focusing on the design aspects that are likely to raise ethical challenges. It discusses four salient questions to be considered when designing a court ODR system, and the resulting ethical tensions that are brought to the fore. As a fourth party, the ODR system not only replaces existing court functions, but enlarges the scope of the courts’ intervention in disputes and increases the courts’ interface with the user. Furthermore, certain ethical principles such as transparency, accountability, impartiality and fairness take on greater significance in the court context than in private ODR, because of the association of the courts with substantive and procedural justice. As in any dispute resolution system, a coherent and effective court ODR system should be guided by dispute system design principles, which includes having clarity of the system’s underlying values and purposes. It is therefore pertinent for each court to resolve the key ethical tensions in order to articulate the foundational values that will undergird the design of its ODR system.